EKONOMI ISLAM: KAJIAN KONSEP DAN MODEL PENDEKATAN (Mazahib, 2007)
This article is to describe Islamic views on economy as they have been enhsrined in the Koran. There are at least three explanations of what constitute Islamic economy: first, the science of Islamic economy; second, the system of Islamic economy, third, the economy of Muslim. The emergence of Islamic economy is very much to do with the doctrine of riba prohibition. In its modern practice, banking interest is deemed to be riba. In addition, the study of Islamic economy in modern time has been undertaken by means of different approaches.